ANALYSIS INFLUENCE OF E-PROCUREMENT AGAINST GOOD GOVERNANCE IN KEMENTERIAN AGAMA REPUBLIK OF INDONESIA - Budidharma, G.N. Hadi (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2019)
Good governance is based on the implementation of government legislation, public policies that are transparent, as well as the participation and public accountability. Institutions of good governance includes the state or the government, private sector or the business world and society. Good governance is defined as the activity of the synergistic relationship between the state, private sector and communities. The utilization of information and communication technology in government or often called e-procurement with good information technology support and implementing integrity is believed to be vital in attaining good governance. Through the implementation of e-procurement, is expected various principles of good governance are able to materialize in governance so that corruption and bad actions in the governance process can be eliminated. This study aims to demonstrate empirically the effect of e-procurement to good governance in the ministry of religious institutions. The method of statistical analysis used is multiple regression. These results indicate that e-procurement is measured by principles such as efficient, effective, transparent, open, fair and accountable have a significant impact on good governance, while the principle of competitiveness does not have a significant effect on good governance